2016
DOI: 10.3762/bjoc.12.172
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linked cyclodextrin-based material for treatment of metals and organic substances present in industrial discharge waters

Abstract: SummaryIn this study, a polymer, prepared by crosslinking cyclodextrin (CD) by means of a polycarboxylic acid, was used for the removal of pollutants from spiked solutions and discharge waters from the surface treatment industry. In spiked solutions containing five metals, sixteen polycyclic aromatic hydrocarbons (PAH) and three alkylphenols (AP), the material exhibited high adsorption capacities: >99% of Co2+, Ni2+ and Zn2+ were removed, between 65 and 82% of the PAHs, as well as 69 to 90% of the APs. Due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 32 publications
(31 reference statements)
2
24
0
Order By: Relevance
“…This coating can be easily observed on SEM images [Figure (d)]. Indeed, our results showed that the COO – groups are responsible for metal ion binding through electrostatic interactions and ion‐exchange, and their presence in Hemp 2A positively influenced its performance. In addition the electrostatic repulsions among the carboxylate anions resulted in the swelling of the polymer network and the increase in the size of the pores, also favoring the metal adsorption.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…This coating can be easily observed on SEM images [Figure (d)]. Indeed, our results showed that the COO – groups are responsible for metal ion binding through electrostatic interactions and ion‐exchange, and their presence in Hemp 2A positively influenced its performance. In addition the electrostatic repulsions among the carboxylate anions resulted in the swelling of the polymer network and the increase in the size of the pores, also favoring the metal adsorption.…”
Section: Resultsmentioning
confidence: 61%
“…Thus, metal ions can easily diffuse inside and outside: the high performance obtained for modified hemp can be explained both the presence of surface adsorption, diffusion, and chemisorption mechanisms. During the curing step at 160 °C of the felt process, two out of the four carboxylic functions of BTCA reacted with both the anhydroglucose units of MALTO and cellulose to form the polymer network, thus the two residual free carboxylic groups remained available to react with cations through chemisorption …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An analysis of all the chemical and biological results showed that an additional treatment with hemp represents an interesting tool for decreasing the environmental impact of industrial effluent. Besides both types of hemp materials presented performances in a lesser extent reduction for waters parameters (e.g., nitrites, total P, and HI) and in removal of organic contaminants due an absence of specific interaction between these substances and the materials . This limit could be circumvented in case a cyclodextrin was used in place of maltodextrin.…”
Section: Discussionmentioning
confidence: 99%